Associations of maternal and placental extracellular vesicle miRNA with preeclampsia - Aharon, Anat; Rebibo-Sabbah, Annie; Ahmad, Rawan Sayed; Dangot, Ayelet; Bar-Lev, Tali Hana; Brenner, Benjamin; Cohen, Adi Halberthal; David, Chen Ben; Weiner, Zeev; Solt, Ido (Frontiers in Cell and Developmental Biology, 2023)
Introduction: Gestational vascular complications (GVCs), including gestational hypertension and preeclampsia, are leading causes of maternal morbidity and mortality. Elevated levels of extracellular vesicles (EVs), in GVC have been linked to vascular injury. This study aims to characterize placental and circulating EV miRNA in GVCs, and explores the involvement of EV-miRNA in GVC, and whether they may be used to distinguish between placental and maternal pathologies. Methods: Blood samples were obtained from 15 non-pregnant (NP), 18 healthy-pregnant (HP), and 23 women with GVC during the third trimester. Placental sections were obtained after caesarian section. Platelet-poor-plasma (PPP) and EV pellets were characterized: EV size/concentration, protein content and miRNA expression were measured by nanoparticle tracking analysis, western blot, nano-string technology and RT-PCR. The effects of EVs on trophoblasts and EC miRNA expression were evaluated. Results: Higher EVs concentrations were observed in HP-PPP and GVC-PPP (P<0.0001) compared to the NP-PPP. The concentration of large EVs (>100nm) was higher in PPP and EV pellets of HP and GVC compared to the NP group. EV pellets of pregnant women demonstrated lower expression of exosomal markers CD63/CD81 compared to NP-EVs. GVC-EVs expressed more human placental lactogen (hPL) hormone than HP-EVs, reflecting their placental origin. Screening of miRNAs in EV pellets and in PPP identified certain miRNAs that were highly expressed only in EVs pellets of the HP (13%) and GVC groups (15%), but not in the NP group. Differences were detected in the expression of hsa-miR-16-5p, hsa-miR-210, and hsa-miR-29b-3p. The expression of hsa-miR-16-5p and hsa-miR-210 was low in EV pellets obtained from NP, higher in HP-EVs, and significantly lower in GVC-EVs. Except for hsa-miR-29b-3p, which was upregulated in GVC, no significant differences were found in the levels of other miRNAs in placental sections. Exposure to GVC-EVs resulted in higher expression of hsa-miR-29b-3p compared to cells exposed to HP-EVs in villous trophoblasts, but not in EC. Conclusions: Expression of hsa-miR-16-5p and hsa-miR-210 reflects maternal pathophysiological status, while hsa-miR-29b-3p reflects placental status. These findings suggest that EV-miRNA are involved in GVC, and that they may be used to distinguish between pathologies of placental and maternal origins in preeclampsia.